2003
DOI: 10.1142/s021849580300007x
|View full text |Cite
|
Sign up to set email alerts
|

Family Enterprises as an Important Factor of the Economic Development: The Case of Slovenia

Abstract: Family SMEs represent an important share in the structure of all enterprises world-wide. In Slovenia, until recently we did not have at our disposal data or leastwise estimates on the share of the family enterprises as insufficient attention was devoted to their investigation. However, if we proceed from the fact that in Slovenia, especially in the 1990s, the number of SMEs has dramatically increased, it can be assumed that family enterprises also present a significant factor of the economic development in Slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 3 publications
0
22
0
4
Order By: Relevance
“…Some study (Quddus and Rashid, 2000) reports myriad of bureaucratic obstacles that entrepreneurs face in their quest to start a business. A host of factors such as lack of long-term capital (Chowdhury and Amin, 2011), limited personal and family savings (Mintoo, 2006), limited access to market (Keh, Nguyen and Ng, 2007;Mead and Liedholm, 1998;Swierczek and Ha, 2003), technology (Gundry, Ben-Yoseph and Posig, 2002;Gibbons and O'Connor, 2003) and information (Singh and Krishna, 1994;Duh, 2003;Kriestiansen, 2002) have been found to be impeding the success of entrepreneurs of small and medium enterprises of Bangladesh. Personal and political enmity between political rivals, frequent haratal (strikes), lack of respect for elementary principles of democratic governance have become the principal characteristics of political system of the country (Chowdhury, 2007).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Some study (Quddus and Rashid, 2000) reports myriad of bureaucratic obstacles that entrepreneurs face in their quest to start a business. A host of factors such as lack of long-term capital (Chowdhury and Amin, 2011), limited personal and family savings (Mintoo, 2006), limited access to market (Keh, Nguyen and Ng, 2007;Mead and Liedholm, 1998;Swierczek and Ha, 2003), technology (Gundry, Ben-Yoseph and Posig, 2002;Gibbons and O'Connor, 2003) and information (Singh and Krishna, 1994;Duh, 2003;Kriestiansen, 2002) have been found to be impeding the success of entrepreneurs of small and medium enterprises of Bangladesh. Personal and political enmity between political rivals, frequent haratal (strikes), lack of respect for elementary principles of democratic governance have become the principal characteristics of political system of the country (Chowdhury, 2007).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…For Slovenia, several estimations were done regarding the importance of family businesses. The estimated share of family enterprises among SMEs in one Slovenian region ranged between 38.1 and 50.1 percent (Duh, 2003). The results of another large-scale research study showed that 46.45 percent of SMEs in the sample were identified as family businesses; the estimated share of family enterprises among SMEs in Slovenia was between 41.11 and 51.79 percent .…”
Section: Family Businesses As An Important Factor Of Economic Developmentioning
confidence: 88%
“…Indeed, the social and economic changes in the former socialist countries in the Central and Eastern Europe created an opportunity for establishing private enterprises, and the industrial policy in these countries has been focused on the development of a dynamic SME sector. Several studies have found that families provide critical resources and support to newly emerging enterprises in these countries (Duh, 2003;Dyer & Panicheva Mortensen, 2005;Poutziouris et al, 1997).…”
Section: Family Businesses As An Important Factor Of Economic Developmentioning
confidence: 99%
See 2 more Smart Citations